The role of amniocentesis in genetic anomaly detection - Ibnu Pranoto, Ibnu Pranoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
Since the beginning of the Landsteiner era, genetics has been developing tremendously. Genetics now is used in genetic counselling, genetic screening and in the management of genetic disorders or diseases due to the fast technological development during the last two decades.Amniocentesis, one of the products of this technological development, is indeed valuable, as it can detect any chromosomal abnormality of the fetus in utero, thus genetic defects among babies, can be prevented.By taking 10-20 ml of amniotic fluid during 14-16 weeks of gestation by amniocen tesis, disposed fetal cells in the fluid can be immediately cultured. After 2-3 weeks, chromosomal analysis can be undertaken to make its karyotype. Other than the above benefit, amniocentesis can also be used for detection of any biochemical abnormality of the fetus, thus early prevention of biochemical disorders among babies can be done.With the application of amniocentesis as one of the diagnostic tools which continuously improves, its benefits help human beings in the prevention of birth defects and in counselling couples who are expecting healthy babies in their marriage.To extend the beneficial aspect of amniocentesis to grass-root level, improvement of knowledge and skills of amniocentesis of practicians is mandatory.Key Words: amniocentesis - amniotic cell culture - chromosomal analysis - genetic counselling -prevention of birth defects